2011
DOI: 10.14310/horm.2002.1324
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of a hormonally active adrenocortical tumor in an adolescent leading to delayed diagnosis

Abstract: Adrenocortical tumors are rare in children and present with variable signs depending on the type of hormone excess. We herein describe the unusual presentation of a child with adrenocortical tumor and introduce the concept of in vitro chemosensitivity testing. cAsE rEPOrt: A 10.5-year-old girl presented with hypertrichosis/hirsutism and weight loss. the weight loss and behavioral problems, associated with halted puberty and growth, led to the initial diagnosis of anorexia nervosa. However, subsequent weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Hagemann et al (9) have reported that approximately 90% of pediatric ACCs are hormonally active and the type of hormone secretion can lead to varied clinical presentations. As illustrated by this case, signs of androgen hyper-secretion can include accelerated growth velocity, bone age advancement, clitoromegaly, and premature adrenarche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hagemann et al (9) have reported that approximately 90% of pediatric ACCs are hormonally active and the type of hormone secretion can lead to varied clinical presentations. As illustrated by this case, signs of androgen hyper-secretion can include accelerated growth velocity, bone age advancement, clitoromegaly, and premature adrenarche.…”
Section: Discussionmentioning
confidence: 99%
“…Ng and Libertino (10) have postulated that the phenotypic presentation of ACC in childhood allows for easier and earlier detection, while Hagemann et al (9) have suggested that particularly in cases of mixed steroid excesses, variations in clinical manifestations may actually delay diagnosis. Michalewicz et al (6) pointed out that these children often do not appear to be ill and in fact their accelerated growth in the early stages can initially be mistaken as a sign of health.…”
Section: Discussionmentioning
confidence: 99%